The Corrosion Performance Of Coupled Zinc Anode-Mild Steel Attachment Methods In Malaysian Seawater - Lim, Chun Ming (Universiti Sains Malaysia, 2017)
Marine corrosion is causing severe problem to the Royal Navy Malaysia, where the navy ship hull is corroded and causing the navy ship to idle from operations. High budget is required to maintain and repair the ship hull. With this, study of this paper is to help to minimise the corrosion rate of ship hull by introducing the sacrificial anode cathodic protection. In this paper of study, corrosion performance of zinc anode coupled with mild carbon steel, which represents the ship hull is studied. Zinc which is more anodic compared to carbon steel tends to corrode when coupled. This is preventing the steel ship hull from corroding and lower down the corrosion rate. In this study, the method of attaching zinc anode to the ship hull is studied to find out the performance of them in protecting the carbon steel in term of corrosion rate and polarization resistance. Besides that, the corrosion mechanism of zinc anode coupled with steel is also one of the studies. The experimental work performed involved the technique of electrochemical analysis. Besides the attachment method, environmental effect in seawater such as temperature and velocity of seawater is studied to know the effect of these factors towards the corrosion performance of coupled zinc anode and mild carbon steel. The results of experimental shows that coupled zinc and carbon steel through attachment method of bolting at 45 ºC; 200 rpm has highest corrosion rate of 1.202 × 10-2 mm/year compared to the lowest corrosion rate of 1.061 × 10-4 mm/year from method of casting; 45 ºC; 0 rpm.